IBU SEBAGAI PEMBENTUK KEMANDIRIAN ANAK USIA DINI DI LINGKUNGAN KELUARGA - Eko Sulistyasih (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
This paper is intended to describe the role played by mothers in building early childhood independence. Independence is defined as a state of things or can stand on its own without relying on others. There are six roles performed by the mother in the form of independence in early childhood. First, give yourself positive understanding of early childhood.Second, educate early childhood accustomed neatly. Third, giving the game to establish independence early childhood. Fourth, provide early childhood choice according to their interests. Fifth, get children early age to behave according to the etiquette. Sixth, to motivate early childhood so as not lazy.Â